Flood Evacuation Modelling in Reducing the Potential Loss of Life from Catastrophic Flooding Due to Dam Failure: The Approach of Life Safety Model (LSM) - Norkhairi F.F.; Hasini H.; Muda R.S.; Thiruchelvam S. (Springer Science and Business Media Deutschland GmbH, 2024)
The Life Safety Model (LSM) is an agent-based model used to estimate the loss of life in catastrophic flooding. By using the agent-based model concept, LSM is able to integrate the 2D hydraulic model with the agents, leading to the fate of the agents. The results from the LSM simulation can be used to support evacuation planning, especially at the community level. In this study, the approach of LSM can identify the factors contributing to the loss of life through the simulation of various cases in the study area. From the simulation, the results show that timely flood warning dissemination, delayed response time and safe location play an important factor in reducing the number of fatalities. When there is sufficient warning time provided, People at Risk (PAR) can evacuate to a safe location within the time provided together with the quick response from PAR itself. However, in some situations, a delay in response time can reduce the number of fatalities. Along with the timely warning, the safe location needs to be suitable and can be reached by populations in the shortest time. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.